Analisa Pengaruh Nozzle pada Ruang Bakar Terhadap Kinerja Turbin Gas Mikro - Irgi Maulana Qutby (Fakultas Teknik, 2025)
This study aims to investigate the effect of nozzle variations on the performance of a micro gas turbine engine using LPG fuel. Gas turbines are mechanical driving machines that utilize compressed air to generate mechanical energy. Micro gas turbines are gas turbines with electrical power below 200 kW. The main components of a gas turbine include a compressor, combustion chamber, turbine, and generator. The performance of a micro gas turbine depends on the control of fuel and air inputs, as well as the mass ratio between them. Parameters such as compressor work, turbine work, back work ratio, net work, and thermal efficiency are used to measure the performance of micro gas turbines. In this study, nozzle variations were performed on the micro gas turbine. The results show that the single-hole nozzle variation exhibits higher ideal and net turbine performance compared to the 7-hole nozzle variations. However, the single hole variations have higher Back Work Ratios (BWR), indicating better efficiency. Additionally, thermal efficiency is influenced by the inlet and outlet temperatures of the turbine generated by each nozzle variation. The single-hole nozzle variation achieves the highest thermal efficiency of 80,6% at a fuel mass flow rate of 26,61 l/min, while the 7 hole nozzle variations reach the highest thermal efficiency of 45,4% at a fuel mass flow rate of 17,89 l/min.
Reupload File Repository_Yudi :: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Pengaruh Variasi Nozzle; Ruang Bakar; Turbin Gas Mikro